Effects of an Herbal Combination on Glycemic Control and Lipid Profile in Diabetic Women: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Reyhaneh Shokoohi PhD; Saeed Kianbakht PhD; Mohammad Faramarzi PhD; Masoud Rahmanian PhD; Farzaneh Nabati PhD; Saeed Mehrzadi PhD; Hasan Fallah Huseini PhD (SAGE Publishing, 2017)
The present study was conducted to explore the efficacy and safety of a herbal combination in the treatment of women with hyperlipidemic type 2 diabetes. The herbal combination capsule (600 mg) contained Terminalia chebula fruit extract (200 mg), Commiphora mukul (200 mg), and Commiphora myrrha oleo-gum-resin (200 mg), and the placebo capsule contained 600 mg toast powder. The patients in one group took the herbal combination and those in the other group took placebo capsules 3 times a day for 3 months. In the herbal combination-treated patients, the fasting blood glucose, total cholesterol, and low-density lipoprotein cholesterol levels were decreased and hidh-density lipoprotein cholesterol levels was increased significantly at the endpoint compared with the placebo and baseline. Other blood parameters such as glycosylated hemoglobin, triglyceride, blood urea nitrogen, creatinine, SGOT, and SGPT levels were not significantly changed after 3 months in both groups. In conclusion, the herbal combination improves glycemic control and lipid profile in women with hyperlipidemic type 2 diabetes without any adverse events.